Enhancing Graduate Teacher Employability on the Complex and Volatile Labour Markets (British Journal of Multidisciplinary and Advanced Studies, 2025)
The levels of unemployment amongst the graduate teachers on the labour market have been increasing at an alarming rate. Every year, huge numbers of new graduates from institutions of higher learning are being offloaded on the market.  Several institutions of higher learning however, have recorded sudden declines on the avarege numbers of enrollments per year. If the trends continue on the same trajectory, the future of teaching as a profesión will continue to remain clouded with high levels of uncertaininty. Several critical questions therefore have been posed as to whether graduate teacher education is still relevant to society today. As the labour market evolves, the graduate teacher education on the other hand has relatively remained static for many years.  There is a close relationship between education and employability. Normally, education enhances employability. It has therefore become an urgent matter within the public domain to look for solutions to address this complex problem.  This article therefore aimed at exploring how graduate teachers employability may be enhanced on the labour market. The researcher employed an embedded mixed methods research design which was grounded in pragmatism. Data was collected using both purposive and simple random sampling techniques. The quantitative data was analysed using inferrential and descriptive statistics while content thematic análysis was used to analyse qualitative data. The results indicated that there was need to consider graduate upskilling and reskilling for enhanced graduate teacher employability on the labour market. It was recommended further that the government could actively lead in the process of graduate teacher education and transformational processes through specific policy direction, robust curriculum reviews and continuos quality improvement.